2018
DOI: 10.1093/ibd/izy077
|View full text |Cite
|
Sign up to set email alerts
|

Similar Inhibition of Dynamic Adhesion of Lymphocytes From IBD Patients to MAdCAM-1 by Vedolizumab and Etrolizumab-s

Abstract: Dynamic adhesion assays are an easy and broadly applicable method for IBD research that is useful for future translational studies and potentially also for supporting clinical treatment decisions. 10.1093/ibd/izy077_video1izy077_Video_15786486962001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…However, another study reported that response to vedolizumab was associated with pre-therapeutic composition of the intestinal microbiome [29]. Moreover, we had suggested that dynamic changes in the expression of α4β1 on peripheral blood CD4 + T cells in the early course of vedolizumab treatment and the baseline dynamic adhesion of CD4 + T cells to MAdCAM-1 in vitro might predict subsequent therapeutic response [17,20].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, another study reported that response to vedolizumab was associated with pre-therapeutic composition of the intestinal microbiome [29]. Moreover, we had suggested that dynamic changes in the expression of α4β1 on peripheral blood CD4 + T cells in the early course of vedolizumab treatment and the baseline dynamic adhesion of CD4 + T cells to MAdCAM-1 in vitro might predict subsequent therapeutic response [17,20].…”
Section: Discussionmentioning
confidence: 95%
“…Taken together, our data suggest that determining the baseline adhesion of CD4 + T cells to MAdCAM-1 and their response to vedolizumab in vitro with the proposed assay may be suitable as a functional biomarker and help to support treatment decisions in most patients. It is important to mention, thatbased on previous observations [17] differential levels of CD4 + T cell adhesion to MAdCAM-1 are most likely not a result of differential α4β7 integrin expression, but rather differential intrinsic functionality of this pathways in responders vs. nonresponders.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Suspensions of 1.5 million cells/mL in adhesion buffer (pH 7.4, 150 mM NaCl, 10 mM HEPES, 1 mM CaCl 2 , 1 mM MgCl 2 , 1 mM MnCl 2 ) were prepared and etrolizumab-s was added or not to aliquots of so far untreated cells. Capillaries for dynamic in vitro adhesion assays were prepared as previously described (Binder et al, 2018). In brief, miniature borosilicate capillaries (Vitrocom) were coated with 5 μg/mL rhMAdCAM-1-Fc-chimera (R&D Systems) in 150 mM NaCl with 10 mM HEPES for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%